2022
DOI: 10.3390/jcm11216351
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and Eye Screening: Diabetic Patients Standpoint, Their Practice, and Barriers; A Cross-Sectional Study

Abstract: Diabetes mellites (DM) is one of the most common systemic disorders in Saudi Arabia and worldwide. Diabetic retinopathy (DR) is a potentially blinding ophthalmic consequence of uncontrolled DM. The early detection of DR leads to an earlier intervention, which might be sight-saving. Our aim in this cross-sectional study is to assess patients’ knowledge and practices regarding DR, and to detect the barriers for eye screening and receiving a check-up from an ophthalmologist. The study included 386 diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Other referrals were provided for visually significant cataract (n = 1684, 51.14%), age-related macular degeneration (n = 256, 7.77%), glaucoma (n = 68, 2.06%), and other reasons (n = 20, 0.61%). Re-screening guidelines of the Early Treatment Diabetic Retinopathy Study classification were used to advise follow-up to all other patients [9,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Other referrals were provided for visually significant cataract (n = 1684, 51.14%), age-related macular degeneration (n = 256, 7.77%), glaucoma (n = 68, 2.06%), and other reasons (n = 20, 0.61%). Re-screening guidelines of the Early Treatment Diabetic Retinopathy Study classification were used to advise follow-up to all other patients [9,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…An alarming 75.1% of T2DM patients expressed unawareness of the recommended frequency of eye checks. In contrast, a study conducted in Saudi Arabia revealed that 73.3% of diabetic patients were aware of the need for regular eye check-ups ( 35 ). The significant knowledge gap observed in our study regarding screening for DR may be attributed to a lack of understanding about the importance of eye screening.…”
Section: Discussionmentioning
confidence: 97%
“…DR is a retinal complication of prolonged DM that affects the retinal microvasculature [ 32 ]. As a result, the longer the duration of DM, the higher the risk of developing DR or sight-threatening DR is usually considered.…”
Section: Discussionmentioning
confidence: 99%